Avoidance of axonal stimulation with sinusoidal epiretinal stimulation - Corna, Andrea; Cojocaru, Andreea-Elena; Bui, Mai Thu; Werginz, Paul; Zeck, Günther (Journal of neural engineering, 2024)
Neuromodulation, particularly electrical stimulation, necessitates high spatial resolution to achieve artificial vision with high acuity. In epiretinal implants, this is hindered by the undesired activation of distal axons. Here we investigate focal and axonal activation of Retinal Ganglion Cells (RGCs) for different sinusoidal stimulation frequencies. Our results can be exploited to define a selective stimulation strategy to avoid axonal activation in retina implants. RGC responses to epiretinal sinusoidal stimulation at frequencies between 40 and 100 Hz were tested in ex-vivo photoreceptor degenerated (rd10) retina explants. Experiments were conducted using a high-density CMOS-based Micro Electrode Array, which allows to locate RGC cell bodies and axons with high spatial resolution while performing simultaneous recording and stimulation. We report current and charge density threshold for focal and distal axon activation for sinusoidal stimulation at 40, 60, 80 and 100 Hz, in the order of 0.5 µA. We identify selective stimulation for 40 and 60 Hz up to 0.23 and 0.28 µA (173 and 148 nC/mm ), showing how the selective stimulation window increases when reducing the stimulation frequency. With the use of synaptic blockers, we demonstrate the underlying direct activation mechanism of the ganglion cells. Finally, with the use of high resolution electrical imaging and axon tracking, we investigated the extent of the activation in axonal bundles. . 40 and 60 Hz sinusoidal electrical stimulation can be applied to achieve focal activation of RGCs in epiretinal configuration. The presented results can be implemented as a stimulation strategy to avoid axonal stimulation solving one of the major limitations of artificial vision and retina implants. The results could be extended to other fields of neuroprosthetics to achieve selective focal electrical stimulation.